Negative impacts from disruption of road infrastructure element performance on dependent subsystems: methodological framework - Rehak, David; Patrman, David; Foltin, Pavel; Dvořák, Zdeněk; Skrickij, Viktor (Transport, 2021)
The critical infrastructure system is determined by subsystems essential for the functioning of the state (such as energy, transport, and emergency services). Disruption to the function of these subsystems would have serious effects on state security, the state economy, and the provisioning of the inhabitants’ basic human needs. Links connect these subsystems (i.e., sectors, subsectors, and elements), and these links ensure that certain subsystems are integrated into each other. Their interactions are derived from the type and intensity of the mutual link. The interlinked subsystems can thus be divided into influencing and dependent ones. The aforementioned mutual links in the critical infrastructure system allow, amongst other things, the spread of impacts of disruptive events amongst the subsystems via cascading effects. Disruptions to the performance of an influencing subsystem may have negative effects on a dependent subsystem, resulting in the spread of cascading effects in the critical infrastructure system. Such effects are often difficult to predict, which reduces the responsiveness of the dependent subsystems. Road transport is one of the most significant influences on critical infrastructure subsystems. For this reason, the article focuses on an indication of the negative effects of disruption of road infrastructure elements on dependent subsystems. The article describes the role of road infrastructure in the context of the critical infrastructure system. Defines the dependent subsystems of road infrastructure, categorises the negative effects, and presents a possible approach to assessing the adverse effects of disruption road infrastructure performance on dependent subsystems. First published online 10 February 2022